Third Five Year Plan 1961-66 - Planning Commission (Planning Commission, 1967)
Third five year plan—progress of expenditure, summary by sectors, third five year plan—progress of expenditure, scheme-wise details of the third five year plan, details of centrally sponsored schemes for the third plan, details of centrally sponsored schemes for the third plan.
Statements Showing the Actual Expenditure